2018
DOI: 10.1016/j.mcn.2018.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Centella asiatica attenuates hippocampal mitochondrial dysfunction and improves memory and executive function in β-amyloid overexpressing mice

Abstract: Centella asiatica is a medicinal plant used to enhance memory. We have previously shown that a water extract of Centella asiatica (CAW) attenuates β-amyloid (Aβ)-induced spatial memory deficits in mice and improves neuronal health. Yet the effect of CAW on other cognitive domains remains unexplored as does its In vivo mechanism of improving Aβ-related cognitive impairment. This study investigates the effects of CAW on learning, memory and executive function as well as mitochondrial function and antioxidant res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
62
2
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 67 publications
4
62
2
3
Order By: Relevance
“…For instance, Hong et al (2013) used proteomic analysis to demonstrate activation of the NRF2 transcriptional pathway in 5XFAD mice at four months of age [100], which is consistent with ARE activation in Alzheimer's patients [101]. Our laboratory has shown Nrf2 expression, specifically, is elevated further with CAW treatment in seven month old 5XFAD female mice [33], an observation shown in the present study to occur in a CAW dose-dependent manner. This suggests CAW improves antioxidant signaling to combat the ever increasing oxidative stress mediated by the expanding Aβ pathology indicative of AD.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…For instance, Hong et al (2013) used proteomic analysis to demonstrate activation of the NRF2 transcriptional pathway in 5XFAD mice at four months of age [100], which is consistent with ARE activation in Alzheimer's patients [101]. Our laboratory has shown Nrf2 expression, specifically, is elevated further with CAW treatment in seven month old 5XFAD female mice [33], an observation shown in the present study to occur in a CAW dose-dependent manner. This suggests CAW improves antioxidant signaling to combat the ever increasing oxidative stress mediated by the expanding Aβ pathology indicative of AD.…”
Section: Discussionsupporting
confidence: 87%
“…We have confirmed that these mechanisms also operate in aging wild-type (WT) mice [1]. In this study, we expand on our previous studies in female Tg2576 [13] and female 5XFAD mice [33] treated with 200 mg/kg/d CAW. The present study includes 5XFAD mice and WT littermates of both genders and treatment with a range of CAW doses (0, 200, 500, 1000 mg/kg/d).…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…Bar, 25 μm in all images. Quantitation of the cytoplasmic SOD-1 and HO-1 fluorescent signals is shown in Additional file 3: Figure S3 alterations in mitochondrial respiration and ATP production both in neuronal cultures and transgenic mouse models [97][98][99][100][101][102]. In spite of their potential for the development of future therapeutic strategies, the consequences of the prolonged use of Nrf2 activators should be further explored, specially taking into consideration the reported association of Nrf2 exacerbated activation with certain types of cancer [103].…”
Section: Discussionmentioning
confidence: 99%
“…Pathological deposition of Aβ in the brain is a well‐known characteristic of AD (Armstrong, ). Aβ production is associated with impaired hippocampal synaptic plasticity, which leads to behavioral abnormalities (Gray et al, ). In the current study, we observed that IH exposure significantly reduced the number of Aβ plaques in the hippocampus of AD mice.…”
Section: Discussionmentioning
confidence: 99%